The effect of low let (linear energy transfer) ionizing radiation to catalase activity of wistar’s submandibular gland - Nevy T. Putri; Sarianoferni Sarianoferni; Endah Wahjuningsih (Journal of Dentomaxillofacial Science, 2016)
Intraoral periapical radiograph examination is the additional examination which is the most widely used in Dentistry. This radiograph examination using an x-ray ionizing radiation with low LET (Linear Energy Transfer), and may affect submandibular salivary gland. Ionizing radiation exposure can cause damage by inducing a series of changes at the molecular and cellular level. This study aimed to prove the effects of x-ray ionizing radiation with low LET towards the catalase activity of Rattus norvegicus strain Wistar’s submandibular gland. The subjects were 28 male Wistar rats and divided into 4 groups (n=7). Three groups were exposed 4, 8 and 14 times to radiation with 0.002 µSv for each exposure. The catalase activity of each rat was examined by a spectrophotometer. Data were analyzed using one-way ANOVA followed by Bonferroni test. The results showed the average of catalase activity on Wistar rat’s submandibular gland, respectively for: 0.150±0.0895 (KK), 0.1405±0.0607 (K1), 0.1228±0.0290 (K2), 0.1227±0.0556 (K3). Data showed significant differences of catalase activity between test groups, but showed not significant differences of catalase activity between each groups of Rattus norvegicus strain Wistar’s submandibular gland. In this study concluded decreased catalase activity of Rattus norvegicus strain Wistar’s submandibular gland resulting from x-rays ionizing radiation by 4 times, 8 times and 14 times exposures.